2016
DOI: 10.1371/journal.pone.0147223
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Energy Expenditures and Growth Dilution Explain Higher PCB Concentrations in Male Summer Flounder

Abstract: Comparison of polychlorinated biphenyl (PCB) concentrations between the sexes of mature fish may reveal important behavioral and physiological differences between the sexes. We determined whole-fish PCB concentrations in 23 female summer flounder Paralichthys dentatus and 27 male summer flounder from New Jersey coastal waters. To investigate the potential for differences in diet or habitat utilization between the sexes, carbon and nitrogen stable isotope ratios were also determined. In 5 of the 23 female summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Female summer flounder grew sufficiently faster than male summer flounder such that by age 8, females were nearly double the size, by weight, of males [27]. In contrast, the sex differences in growth rates were modest for burbot, sea lamprey, cisco, and lake whitefish [2226].…”
Section: Sex Difference In Pcb Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Female summer flounder grew sufficiently faster than male summer flounder such that by age 8, females were nearly double the size, by weight, of males [27]. In contrast, the sex differences in growth rates were modest for burbot, sea lamprey, cisco, and lake whitefish [2226].…”
Section: Sex Difference In Pcb Concentrationsmentioning
confidence: 99%
“…Thus, in all eight species, whole-fish PCB concentration in males was greater than whole-fish PCB concentration in females. After consideration of all four abovementioned hypotheses, the most likely primary driver of the sex difference in PCB concentrations was consistently identified as a higher rate of energy expenditure rate in males compared with females [ 3 , 7 , 8 , 22 27 ]. The pattern was persistent, regardless of whether the fish species were freshwater or marine.…”
Section: Sex Difference In Pcb Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference in carbon and nitrogen stable isotope ratios between the sexes may reflect a difference in habitat utilization and/or a difference in food habits between the sexes [24,46,47]. However, carbon and nitrogen stable isotope ratios did not significantly vary between the sexes of white suckers from the Kewaunee River population based on the results from an earlier study [48], indicating that this explanation was unlikely.…”
Section: Discussionmentioning
confidence: 80%
“…A difference in carbon and nitrogen stable isotope ratios between the sexes may signal a difference in habitat utilization and/or a difference in food habits between the sexes [1,18,34]. However, in an earlier study, carbon and nitrogen stable isotope ratios were shown not to significantly vary between the sexes of Lake Michigan white suckers that spawn in the Kewaunee River [35], suggesting that this hypothesis was invalid.…”
Section: Discussionmentioning
confidence: 99%